Analysis of the Role of Society in Utilizing Yards as Carbon Emission Reduction - Mu'arif*, M Irvan; Ardiansah, Ardiansah; Sri Budiastuti, Maria Theresia; Utami, Trisni (Universitas Syiah Kuala, 2024)
The increasing population in Bekasi Regency has led to higher demand for housing, vehicles, and industrial areas, resulting in carbon dioxide (CO2) emissions of approximately 8,148,642 tons per year, which negatively impact human health. Residential yards hold significant potential as green spaces that can be developed to enhance carbon absorption through vegetation. This research aims to analyze the role of society in utilizing residential yards to mitigate carbon emissions. The statistical analysis was conducted using the Chi-square test with a significance level of p-value 0.05. The results indicate that the success of planting vegetation in residential yards is significantly associated with age, gender, and education level. However, cultural factors do not show a significant relationship with yard utilization in Bekasi Regency. The most effective yard model for carbon absorption includes diverse vegetation types, particularly perennial plants, which can absorb a greater amount of carbon dioxide. A residential yard with a variety of fruit and perennial plants can absorb approximately 228 kg of CO2 per year for a housing area of 120 m